2019
DOI: 10.1007/s10854-019-00750-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of CdS thin-films from cadmium acetate and ammonium thiosulphate precursors

Abstract: Cadmium sulphide (CdS) thin-films have been electrodeposited using two electrode system to be used as the hole back diffusion barrier (hbdb) layer for graded bandgap solar cells with p-type windows. Cadmium acetate dihydrate [Cd(CH 3 COO) 2 •2H 2 O] and ammonium thiosulphate [(NH 4) 2 S 2 O 3 ] have been used as the cadmium (Cd) and sulphur (S) precursors respectively. In this work, CdS layers have been grown on glass/FTO (fluorine doped tin oxide) substrates at cathodic potentials ranging from 1300 to 1460 mV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
7
11
0
Order By: Relevance
“…In addition, we assume that the conductive ITO layer and the glass substrate on top of which these CdS layers were grown are likely the sources of impurities like Si, Ca, Na, In, and O, whereas Cl originates from the CdCl 2 used in the electrolyte. The obtained results are in good agreement with the earlier reports on electrodeposited CdS thin films 53,54 …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we assume that the conductive ITO layer and the glass substrate on top of which these CdS layers were grown are likely the sources of impurities like Si, Ca, Na, In, and O, whereas Cl originates from the CdCl 2 used in the electrolyte. The obtained results are in good agreement with the earlier reports on electrodeposited CdS thin films 53,54 …”
Section: Resultssupporting
confidence: 92%
“…Simultaneous anodic oxidation of Al on both sides of the glass substrate in order to the creation of AAO templates on both sides of the glass plate 61‐66 Electrochemical deposition of both CdS nanowires and Ni nanotubes in AAO templates on the front and rear sides 54,55,70 Creation of matrices of free‐standing CdS nanopillars and Ni nanotubes simultaneously on the front and back sides of the structure by removing alumina in NaOH solution. Deposition of a thin absorbing p‐CdTe film over an array of CdS nanowires by magnetron sputtering or close spacing sublimation methods 59 …”
Section: Methodsmentioning
confidence: 99%
“…This problem can be solved by employing ammonium thiosulphate ((NH 4 ) 2 S 2 O 3 ) as the S source. Alam et al deposited an n-type CdS film with an electrolyte containing cadmium acetate and ammonium thiosulphate [41]. They found that the deposition resulted in uniform crystalline CdS films with the grain size in the range of 200-300 nm (Figure 4) in the case of the pH value of the solution being about 3 and the temperature being 85 • C.…”
Section: Cdsmentioning
confidence: 99%
“…Therefore, considering the prospects of thin film solar cells based on p-type window layer and inclusion of ebdb and hbdb layers, scientific community should further be focusing on implementing these ideas for CdTe-based devices and other thin film solar cells. Authors' group has already conceptualised CdTe-based devices incorporating both of these ideas and aiming for further developments [65,66].…”
Section: Addition Of Ebdb and Hbdb Layersmentioning
confidence: 99%